Analisis Kebijakan Standar Isi di SMP Miftahul Khoer Boarding School Panjalu Ciamis - Siti Julaeha; Qiqi Yuliati Zaqiah; Supiana Supiana (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The Policy Process Is A Process That Include Activities Planning, Preparation, Implementation, Monitoring And Evaluation Of The Policy, To Be Precisely The Policy At Miftahul Khoer Boarding School Kertamandala Panjalu, Ciamis. In Analyzing To Determine The Strengths And Weaknesses In A Policy So That The Policy Is Right On Target And Appropriately Implemented In An Educational Institution At Several Stages In The Formulation Of The Policy, In Implementation It Is Always In Monitoring And Evaluation So That It Perfects Existing Policies Towards Developments In Accordance With The Culture And The Demands Of The Times And The Community, This Research Analyzes The Policies That Are Determined At Miftahul Khoer Middle School Boarding School Kertamandala Panjalu, Ciamis Precisely the Policy In The Curriculum That Is Defined In The RKJM, RKS, And Poured More Specific On The One Book Of School Curriculum And Subject Teachers At Miftahul Khoer Middle School Boarding School Keywords, Policy Analysis, Miftahul Khoer Middle School